Increasing production diversity and diet quality: Evidence from Bangladesh - Ahmed, Akhter; Coleman, Fiona M.; Ghostlaw, Julie; Hoddinott, John F.; Menon, Purnima; Parvin, Aklima; Pereira, Audrey; Quisumbing, Agnes R.; Roy, Shalini; Younus, Masuma (Wiley, 2024)
In the context of rural Bangladesh, we assess whether agriculture training alone, nutrition behavior communication change (BCC) alone, combined agriculture training and nutrition BCC, or agriculture training and nutrition BCC combined with gender sensitization improve: (a) production diversity, either on household fields or through crop, livestock, or aquaculture activities carried out near the family homestead; and (b) diet diversity and the quality of household diets. All treatment arms were implemented by government employees. Implementation quality was high. No treatment increased production diversification of crops grown on fields. Treatment arms with agricultural training did increase the number of different crops grown in homestead gardens and the likelihood of any egg, dairy, or fish production but the magnitudes of these effect sizes were small. All agricultural treatment arms had, in percentage terms, large effects on measures of levels of homestead production. However, because baseline levels of production were low, the magnitude of these changes in absolute terms was modest. Nearly all treatment arms improved measures of food consumption and diet with the largest effects found when nutrition and agriculture training were combined. Relative to treatments combining agriculture and nutrition training, we find no significant impact of adding the gender sensitization on our measures of production diversity or diet quality. Interventions that combine agricultural training and nutrition BCC can improve both production diversity and diet quality, but they are not a panacea. They can, however, contribute toward better diets of rural households.